Evaluation of population pharmacokinetics and exposure-response relationship with coadministration of amlodipine besylate and olmesartan medoxomil - Rohatagi, Shashank; Carrothers, Timothy J; Kshirsagar, Smita; Khariton, Tatiana; Lee, James; Salazar, Daniel (Journal of clinical pharmacology, 2008)
Population pharmacokinetic models for amlodipine and olmesartan were developed using data collected from 4 phase I studies in healthy volunteers and 1 phase III study in subjects with mild to severe hypertension. A 2-compartment and a 1-compartment model best described the pharmacokinetics of olmesartan and amlodipine, respectively; both agents were characterized by first-order elimination/absorption and an absorption time lag. The analysis shows that neither agent had a clinically significant impact on the clearance of the other. The impact of covariates on the clearance of olmesartan and amlodipine was similar after coadministration of amlodipine besylate and olmesartan medoxomil as separate entities or as a fixed-dose combination compared with monotherapy. The effect of exposure to amlodipine and olmesartan on the change in trough seated diastolic blood pressure was best described by linear and maximum effect (E(max)) models, respectively. Black race was the most important covariate in the exposure-response model, decreasing the maximal possible effect of olmesartan on blood pressure while increasing the effect of amlodipine, without influencing pharmacokinetic parameters. The drug effect of combination therapy was defined on the basis of exposure to both compounds and was greater than the effect of monotherapy with either agent.